2010
DOI: 10.1097/aud.0b013e3181e1d19e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stimulus and Recording Parameters on Spatial Spread of Excitation and Masking Patterns Obtained With the Electrically Evoked Compound Action Potential in Cochlear Implants

Abstract: Objectives Spread of excitation within the cochlea in response to electrical stimulation can be measured with the electrically evoked compound action potential (ECAP). Different spread-of-excitation measurement techniques have been reported in the literature. One method uses a fixed stimulus location while varying the recording electrode along the length of the implanted array. This results in a relatively coarse estimate of spatial spread (SS) along the cochlea. Another method uses a forward-masking paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 26 publications
(82 reference statements)
3
45
0
2
Order By: Relevance
“…ECAP measures required higher stimulus levels than those used for behavioral thresholds because ECAPs were suprathreshold measures obtained with shorter-duration pulse trains, whereas behavioral measures were thresholds obtained with longer-duration pulse trains. The excitation pattern for higher current levels is broader than that for lower levels (e.g., Hughes & Stille, 2010). As a result, each measure likely represents input from slightly different populations of peripheral neurons operating at different discharge rates.…”
Section: Discussionmentioning
confidence: 88%
“…ECAP measures required higher stimulus levels than those used for behavioral thresholds because ECAPs were suprathreshold measures obtained with shorter-duration pulse trains, whereas behavioral measures were thresholds obtained with longer-duration pulse trains. The excitation pattern for higher current levels is broader than that for lower levels (e.g., Hughes & Stille, 2010). As a result, each measure likely represents input from slightly different populations of peripheral neurons operating at different discharge rates.…”
Section: Discussionmentioning
confidence: 88%
“…There is a tendency for channel-interaction functions to broaden with stimulus level at least in some individuals and for some probe electrodes (e.g. Abbas et al 2004; Eisen & Franck 2005; Hughes & Stille 2010); however, speech-perception scores do not decrease with increasing stimulation level (Firszt et al 2004). Even in the normal auditory system, tonal response patterns broaden with level (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Other studies have reported a reduced spread of excitation using forward masking ECAP paradigms [Hughes and Abbas, 2006;Basta et al, 2010;Hughes and Stille, 2010] with improved spectral discrimination. Taken together, these studies demonstrate that perimodiolar electrode arrays achieve their primary design goals.…”
Section: Introductionmentioning
confidence: 99%